Molecular and Ampelographic Characterization of Genotypes Used for Pajarete Wine, an Old Denomination of Origin from Huasco and Elqui Valleys in Northern Chile - Ganga-Munoz, M (Bundesanstalt fur Zuchtungsforschung an Kulturpflanzen, 2022)
The characterization of 30 grape accessions used to produce Pajarete wine is presented, one of the first American "Denomination of Origin" (D.O.). Accessions were collected from small vineyards from the Huasco Valley in the Atacama Region, northern Chile, which are very heterogeneous for varietal assortment, as was demonstrated by microsatellite marker analysis. Eighteen different genotypes were identified, including the two varieties considered the founders of American viticulture, Listán Prieto (syn. País ) and Muscat of Alexandria . A series of criolla varieties was also identified, some of them already described plus others not yet included in international databases. Based on nine SSR markers, allelic matchings suggest that four of these new criolla varieties (NN-311, NN-313, NN-368 and NN-370) derives from Listán Prieto x Muscat of Alexandria , but three (NN-314, NN-276 and NN-369) are derived from M. of Alexandria crossed with a yet undetermined parent. Seven criolla accessions were described by ampelography, including some not yet recorded in the European Vitis International Variety Catalogue (VIVC) or in the Instituto de Investigaciones Agropecuarias (INIA) database. Three accessions were considered as not appropriate for the production of Pajarete wine since two of them are table grape varieties and the other is the American variety Isabella (Vitis labrusca x V. vinifera), all considered of poor quality for winemaking. All these findings are very useful to direct the conservation of this unique germplasm, as well as for small producers of Pajarete wine, since based on this information on the overall variety assortment of the area, they can now make informed decisions to improve their vineyard management and wine production. © The author(s).